Latihan Berjalan Meningkatkan Kekuatan Otot dan Keseimbangan pada Lansia dengan Risiko Jatuh: A Scoping Review - Sari, Citra Windani Mambang; Rahma, Valenty Rafaustine; Jatiningtyas, Kurnia; Salsabella, Edellweisse Silvia; Dinan, Nur Azmina; Masroorianissa, Aulia Fauzia; Hidayatulloh, Parwiin Salma Zaenab (Poltekkes Kemenkes Banjarmasin, 2023)
Introduction: Falling is one of the most important symptoms and the main etiology of morbidity and mortality for the elderly aged 65 years. In the elderly who are at risk of falling, stretching (flexibility) and balance exercises are recommended in the physical activity program. This literature review aims to identify whether walking exercises are effective in reducing the risk of falling in the elderly and to find out whether walking exercises can train muscles and balance in the elderly.Method: The method used is scoping review. Literature searches were obtained from several databases of Cinahl Plus, Pubmed, and Springer by applying the keywords